Co-optimising frequency-containment services from zero-carbon sources in electricity grids dominated by Renewable Energy Sources - Aimon Mirza Baig; Luis Badesa; Yi Wang; Goran Strbac (International Journal of Electrical Power & Energy Systems)
Power systems dominated by Renewable Energy Sources (RES) are characterised by reduced levels of inertia, which in turn threaten the security of the electricity grid, and significantly increase the requirement for ancillary services such as inertia and Frequency Response (FR). Since inertia and FR are typically provided by part-loaded thermal generators, system security and carbon emissions are still highly coupled. Therefore, it becomes critical to investigate alternative ways to guarantee grid stability without resorting to polluting assets, as emissions targets would be unattainable otherwise. In this context, the present paper introduces a frequency-security constrained Stochastic Unit Commitment (SUC) model, which simultaneously co-optimises clean services such as inertia from Synchronous Condensers (SCs) and FR from part-loaded RES and Battery Energy Storage System (BESS). A methodology is proposed to capture the dynamics for inertia from SCs, Primary Frequency Response (PFR) from RES and Enhanced Frequency Response (EFR) from BESS in the form of linear constraints. The ancillary services dynamics are then mapped into the optimisation through frequency-security constraints obtained by solving the swing equation, eventually formulated as a Mixed-Integer Second-Order Cone Program (MISOCP). The proposed constraints enforce that sufficient ancillary services are scheduled to maintain system stability, while taking advantage of the economic savings and emissions reduction from zero-carbon sources. Finally, to provide a rigorous quantification of the benefits of co-optimising the provision of zero-carbon ancillary services, a 2030 Great Britain (GB) power system scenario is used. The results demonstrate that ancillary services costs can be reduced from 35% to 3.3% and 45% to 4.2% of the total system operating cost under wind scenarios of 70GW and 100GW respectively. Similarly, simulations demonstrate that the provision of ancillary services can significantly reduce emissions in the system.